Cytomegalovirus as a potential trigger for systemic lupus erythematosus: a case report. (December 2015) - Yamazaki, Susumu; Endo, Amane; Iso, Takashi; Abe, Shinpei; Aoyagi, You; Suzuki, Mitsuyoshi; Fujii, Toru; Haruna, Hidenori; Ohtsuka, Yoshikazu; Shimizu, Toshiaki
Abstract Background The role of cytomegalovirus infection in triggering systemic lupus erythematosus remains a subject of debate. Here, we present a case of childhood systemic lupus erythematosus with concomitant cytomegalovirus infection, which sheds light on the relationship between these conditions and their treatment in pediatric patients. Case presentation A 12-year-old Japanese girl with no history of systemic illness was diagnosed with systemic lupus erythematosus and concomitant primary cytomegalovirus infection. Her anti-cytomegalovirus immunoglobulin G antibodies were elevated during diagnosis and treatment. Further, the patient's cytomegalovirus pp65 antigenemia level was slightly elevated (1 cell per 5 × 104 cells). Treatment included the administration of ganciclovir, prednisolone, methylprednisolone, and cyclophosphamide, none of which prompted adverse effects. The patient was in good condition at the most recent follow-up. Conclusion Ganciclovir treatment is not completely safe, and there are no clinical guidelines regarding its use in patients with systemic lupus erythematosus triggered by cytomegalovirus infection. Our experience with this case suggests that the decision to administer ganciclovir treatment in pediatric cases should be guided by a variety of factors in addition to the cytomegalovirus antigenemia level. These factors include lymphopenia, renal biopsy results, and cytomegalovirus DNA levels detected by polymerase chain reaction. The details of our patient's presentation and treatment should prove illustrative to other clinicians who face similar cases.